Review essay: A surfeit of violence? - Exertzoglou, Haris (Historein, 2014)
Review article of Ayşe Ozil, Orthodox Christians in the Late Ottoman Empire: A Study of Communal Relations in Anatolia, London: Routledge, 2013; Nicholas Doumanis, Before the Nation: Muslim–Christian Coexistence and its Destruction in the Late Ottoman Anatolia, Oxford: Oxford University Press, 2013; Ryan Gingeras, Sorrowful Shores: Violence, Ethnicity and the End of the Ottoman Empire, 1912–1923, Oxford: Oxford University Press, 2011.